Entre a tolerância e o estigma: a condição dos judeus na legislação de Afonso X (Castela - séc. XIII) - Portela, Ludmila Noeme Santos (2020)
The purpose of this research is to examine the treatment of Jews in the legislative documents compiled by king Alfonso X of Castile, in the 13th century. We intend to analyze the discursive characteristics of religious stigmatization and legal tolerance t